CEO Compensation and Firm's Cash Holding: A Pitch - Muhammad Atif (Journal of Accounting and Management Information Systems (JAMIS), 2016)
This letter discusses the application of a pitch using Faff (2015a) pitching template, with intention to refine my idea and develop it in a systematic fashion. I find the pitching research template interesting; by applying it to my study that enhances the thought process and helps in precisely developing the idea before presenting it anywhere and starting work on the project. This PRL includes the brief commentary on personal reflection as few sections are quite daunting for junior researchers, but continual discussion is the key to refining the idea.
Keywords: G32; G34; 650; Pitching research; Compensation; Corporate governance; Cash holding; Australia